Professionalization influences on Thai family SMEs internationalization activities - Kotanut, Varitha (2012)
Professionalisation is what has occurred in many family businesses. Recently, Thai family SMEs has become more and more internationalised. My dissertation studied how professionalisation influence firms' internationalisation process, including personnel from whom they acquired relevant skills, specific market knowledge, and experiences that enable growth of the company. These personnel may also affect the firm's managerial system. Each firm may change their governance, strategy, and control system to a more formal as they opt for growth. Moreover, a firm can engage professionalisation at any stages of their business. The assumption is that the earlier they professionalise, the more likely that they internationalised. However, the research from 13 different firms provides more aspects and interesting findings for the topic.